LITERATURE REVIEW: IMPROVING PHYSICS LEARNING OUTCOMES AND CRITICAL THINKING SKILLS OF STUDENTS THROUGH THE PROBLEM-BASED LEARNING MODEL - Sitompul, Loris Jelita; Rahma Dani (Jurnal Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model in improving high school students’ physics learning outcomes and critical thinking skills. The research method used is a literature review by examining 50 relevant classroom action research (CAR) articles obtained from national journals and proceedings. The data were analyzed descriptively and qualitatively through a categorization process based on the research focus. The results of the study show that 28 articles (56%) focused on improving physics learning outcomes, 12 articles (24%) highlighted the development of critical thinking skills, and 10 articles (20%) integrated both. In general, the application of PBL has been proven to improve understanding of physics concepts, learning outcomes, and train students to analyze and evaluate problems critically. These findings confirm that PBL is an effective alternative learning strategy for improving the quality of physics learning in high school.